Multi-agent system for therapy in children with the autistic spectrum disorder (ASD), utilizing smart vision techniques—SMA-TEAVI - Alvelais-Alarcón, Marina (My University, 2020)
The present article shows the analysis and design of a Multi-Agent System’s architecture for Emotional–Social assistance, which will be implemented in a robot, it will perform tasks such as therapy for children diagnosed within the Autistic Spectrum Disorder (ASD). Other tasks the robot will perform are the development of skills in the physical education field, with the goal of improving the motivation and mobility of the children, at the same time, the system will identify the emotions the child expresses, based on Paul Ekman’s basic emotions model.
Agents and multi-agent systems: technologies and applications 2020
Keywords: Autism spectrum disorder; Smart vision techniques; Campus Tijuana